Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð»Ð¾ÐºÐ°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð´Ð¸ÑÑ‚Ð°Ð½Ñ†Ð¸Ð¾Ð½Ð½Ð¾Ð³Ð¾ Ð¸Ð½Ð´ÑƒÑ†Ð¸Ñ€ÑƒÑŽÑ‰ÐµÐ³Ð¾ ÐºÑ€Ð¸Ð¾Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ñ Ð¸ Ñ„Ð°ÐºÑ‚Ð¾Ñ€Ð° Ð²Ñ€ÐµÐ¼ÐµÐ½Ð¸ Ð½Ð° Ð³ÑƒÐ¼Ð¾Ñ€Ð°Ð»ÑŒÐ½Ñ‹Ð¹ Ð¸Ð¼Ð¼ÑƒÐ½Ð¸Ñ‚ÐµÑ‚ Ð±Ð¾Ð»ÑŒÐ½Ñ‹Ñ… Ð³Ð¸Ð¿Ð¾Ñ‚Ð¸Ñ€ÐµÐ¾Ð·Ð¾Ð¼, Ð¾Ð¿ÐµÑ€Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ð¿Ð¾ Ð¿Ð¾Ð²Ð¾Ð´Ñƒ Ð°ÑƒÑ‚Ð¾Ð¸Ð¼Ð¼ÑƒÐ½Ð½Ð¾Ð³Ð¾ Ñ‚Ð¸Ñ€ÐµÐ¾Ð¸Ð´Ð¸Ñ‚Ð° - Mikityuk, M. R.; Karachentsev, Yu. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The influence of local distant inducing cryoeffect (LDIC) and time factor on the immunity humoral link indices in 25 patients with hypothyrosis, operated for autoimmune thyroiditis (AIT), was studied in dynamics. LDIC was shown to cause the positive changes in the system of humoral anti-thyroid immunity for the term more than 6 months. A gradual fading of immune-modulating effect 9 months later stipulates the necessity for a repeated LDIC application.